Muscular balance, core stability, and injury prevention for middle- and long-distance runners - Fredericson, M.; Moore, T. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
This article is intended to provide an understanding of the importance of core musculature to runners and to offer exercises that will help them achieve desired mobility, stability, muscular balance, and neuromuscular control. Please see Table 1 for an example of how to incorporate these exercises into a periodized training program. It is highly recommended, however, that athletes consult a skilled practitioner to address individual needs and maximize results from a program of this nature.